Analysis of experimental data on -delayed proton and -particle emission - Klintefjord, Malin (My University, 2012)
The spin and parity of the resonance level 2645 keV in 20Na have been studied and discussed for decades among physicists, due to the astrophysical importance of the 19Ne(p,)20Na reaction. The level is situated 450 keV above the threshold for (19Ne+p). In this thesis data from an experiment investigating 20Mg -delayed proton emission, done at CERN-ISOLDE, has been calibrated and analyzed in order to obtain pure proton spectra in search for the resonance level. Simulations of energy deposition in the detectors have also been performed for the setup used and for potential future setups. It was found that the setup used was not sufficiently sensitive to put new limits on the population of the 2645 keV state. Therefore different detectors are discussed, which could allow to lower the amount of detected -background and recoils of 16O, from the decay of 20Na. New findings were -particles from -delayed -emission from 21Mg, identified in the used E E telescope.
Keywords: Fysik; Physical Sciences